Analisis Spasial Pupa Ae. Aegypti dan Temporal Faktor Iklim yang Mempengaruhi Insidensi Demam Berdarah - Andreas Purwanto Hari Kusnanto (Fakultas Kedokteran Universitas Gadjah Mada, 2011)
Background: Dengue Haemorrhagic Fever (DHF) is still a health problem in Gowa Regency. The effective way to reduce the incidence of DHF is reducing the vector population. Using the new relatively of vector index, i.e. pupae/person index, is regarded well than some indices to measure the vector density. Yet, a Stegomyia index is still commonly used in present because of practice and simple. Then, all of indices need to be tested by correlate the vector indices with the incidence of DHF. In this study, demographic/pupae survey is used to knowing each of vector indices. Besides, mapping is done to know the disperse pattern of Aedes vector, then knowing the correlation of climate and the incidence of DHF.Objective: Examining the vector indices that can be trusted for routine survey, understanding the epidemiology of Aedes vector by knowing their disperse pattern, and predicting the early season of dengue transmission to prevent increasing of DHF casesMethod: This was an analytic study with cross-sectional design, using the demographic/pupae survey to know pupae/person index and Stegomyia indices by 496 houses. Index score is correlated by the incidence of DHF in RT’s. Tools of ArcGIS are used to testing the spatial analysis, i.e. Average Nearest Neighbor Distance, to know the tendency of pupae clustering. Pearson correlation is used to testing the incidence of DHF by climate.Results and conclusions: There are significantly positive correlations in BI and CI by the incidence of DHF (p<0,05), there are no correlation in HI and pupae/person index by the incidence of DHF. The pupae spots that mapped tend to cluster (p<0,05). There are negative correlations in range of minimum-maximum temperature by the incidence of DHF.Keywords: stegomyia indices, pupae/person index, cluster, climate, Gowa Regency